2014
DOI: 10.12775/ecoq-2013-0009
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian situation in urban environment – history of the common toad Bufo bufo in Kraków (Poland)

Abstract: Abstract. Rapid urbanization processes are not neutral to the environment, especially amphibians. Their double-environment lifestyle makes them particularly vulnerable to negative changes in the environment. Inventory research on batrachofauna carried out in urban areas usually provides data on its current state, but there is little information about changes in its composition over the years. The aim of the study was to investigate the situation of amphibians in urban areas of Kraków (Poland) over the last 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Contrary to our predictions, 43% of its sites have disappeared. A similar decline of these species, especially strong for green toad, has been observed in Kraków and Poznań (Budzik et al 2013;Kaczmarek et al 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Contrary to our predictions, 43% of its sites have disappeared. A similar decline of these species, especially strong for green toad, has been observed in Kraków and Poznań (Budzik et al 2013;Kaczmarek et al 2014).…”
Section: Discussionsupporting
confidence: 79%
“…A decrease in the number of local populations has been observed in southern and western Poland for more than half of the species, including those considered to be locally common (e.g. Pelophylax lessonae, Rana temporaria; Bonk & Pabijan 2010, Budzik et al 2013. Polish amphibians are primarily threatened by habitat loss and degradation due to urbanization (Rybacki & Berger 2003, Budzik et al 2013 and by water contamination (Rybacki & Berger 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Pelophylax lessonae, Rana temporaria; Bonk & Pabijan 2010, Budzik et al 2013. Polish amphibians are primarily threatened by habitat loss and degradation due to urbanization (Rybacki & Berger 2003, Budzik et al 2013 and by water contamination (Rybacki & Berger 2003). In some localities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this species is used with increasingly frequency in attempts to assess the state of environmental pollution (Orton and Routledge 2011; Dobrovoljc et al 2012; Simon et al 2012; Orton et al 2014; Dmowski et al 2015; Pickford et al 2015). Research in urban areas has shown that the number of sites occupied by amphibians, including common toads, has decreased slightly (Budzik et al 2013; Kaczmarek et al 2015). A similar situation is observed in less-urbanised habitats (Orłowski 2007; Beebee 2014).…”
Section: Introductionmentioning
confidence: 99%